Drosophila Condensin II subunit Chromosome-associated protein D3 regulates cell fate determination through non-cell-autonomous signaling - Klebanow, L. R.; Peshel, E. C.; Schuster, A. T.; De, K.; Sarvepalli, K.; Lemieux, M. E.; Lenoir, J. J.; Moore, A. W.; McDonald, Jocelyn A.; Longworth, M. S. (My University, 2017)
The pattern of the Drosophila melanogaster adult wing is heavily influenced by the expression of proteins that dictate cell fate decisions between intervein and vein during development. dSRF (Blistered) expression in specific regions of the larval wing disc promotes intervein cell fate, whereas EGFR activity promotes vein cell fate. Here, we report that the chromatin-organizing protein CAP-D3 acts to dampen dSRF levels at the anterior/posterior boundary in the larval wing disc, promoting differentiation of cells into the anterior crossvein. CAP-D3 represses KNOT expression in cells immediately adjacent to the anterior/posterior boundary, thus blocking KNOT-mediated repression of EGFR activity and preventing cell death. Maintenance of EGFR activity in these cells depresses dSRF levels in the neighboring anterior crossvein progenitor cells, allowing them to differentiate into vein cells. These findings uncover a novel transcriptional regulatory network influencing Drosophila wing vein development, and are the first to identify a Condensin II subunit as an important regulator of EGFR activity and cell fate determination in vivo.
Citation: Klebanow, L. R., Peshel, E. C., Schuster, A. T., De, K., Sarvepalli, K., Lemieux, M. E., . . . Longworth, M. S. (2016). Drosophila Condensin II subunit Chromosome-associated protein D3 regulates cell fate determination through non-cell-autonomous signaling. Development, 143(15), 2791-2802. doi:10.1242/dev.133686
Keywords: Dcap-D3; Knot; Egfr; Serum Response Factor; Dsrf; Vein Development